Blue Photosensitizer with Copper(II/I) Redox Mediator for Efficient and Stable Dye‐Sensitized Solar Cells. (13th September 2020) - Ren, Yameng; Flores‐Díaz, Natalie; Zhang, Dan; Cao, Yiming; Decoppet, Jean‐David; Fish, George Cameron; Moser, Jacques‐E.; Zakeeruddin, Shaik Mohammed; Wang, Peng; Hagfeldt, Anders; Grätzel, Michael
Abstract: Dye‐sensitized solar cells (DSCs) based on copper(II/I) redox mediators have recently achieved notable performance progress through tailoring the ligand structure of the copper complexes, exploiting cosensitization, and introducing an advanced device structure. In order to further improve the power conversion efficiency (PCE), it is imperative to develop wide spectral‐response photosensitizers compatible with the copper(II/I) redox mediators while attaining a high V oc . Herein, a blue photosensitizer coded R7 is reported, which is purposely designed for highly efficient DSCs with copper‐based electrolytes. R7 features a strong electron‐donating segment of 9, 19‐dihydrobenzo[1′, 10′ ]phenanthro[3′, 4′:4, 5]thieno[3, 2‐ b ]benzo[1, 10]phenanthro[3, 4‐ d ]thiophene conjugated with a bulky auxiliary donor N ‐(2, 4′‐bis(hexyloxy)‐[1, 1′‐biphenyl]‐4‐yl)‐2, 4′‐bis(hexyloxy)‐ N ‐methyl‐[1, 1′‐biphenyl]‐4‐amine and the electron acceptor 4‐(7‐ethynylbenzo[ c ][1, 2, 5]thiadiazol‐4‐yl)benzoic acid. The blue dye R7 with bulkier auxiliary donor moiety in the DSC largely outperforms the reference dye R6, which has a smaller bis(4‐(hexyloxy)phenyl)amine donor unit. Transient absorption spectroscopy and electrochemical impedance spectroscopy measurements show that the R7 based DSC has a higher charge separation yield, a higher charge collection efficiency, and lower charge recombination with the copper electrolyte than the R6 based counterpart. A cosensitized system of R7 and Y123 for the DSC presents an outstanding PCE of 12.7% and retains 90% of its initial value after 1000 h of light soaking under 1 sun at 45 °C. Abstract : A blue photosensitizer coded R7 is judiciously designed for dye sensitized solar cells (DSCs) with copper (II/I)‐based electrolyte. The blue dye R7 enables a power conversion efficiency of 12.7% at the air mass 1.5 global condition, while it maintains 90% of its initial value after 1000 h of continuous full sunlight soaking at 45 °C displaying a remarkable photostability.